Space of changeable identity and the margins of literature - Škamperle, Igor (Primerjalna književnost, 2004)
The paper of the author, who is Triestine by birth, grasps in essayistic stylethe social, linguistic and world-view intricacies of Trieste, an exemplary metropolitan, but incomprehensibly disheartened city, and the steep rim of the Trieste Karst behind it. As a complex and contradictory meeting point, Trieste is strongly faced by two identities, Slovenian and Italian. Its literature inscribes in itself unique topographies, a vast panorama of images imbued with distinct philosophies, incongruent ideas and thematic interests.
Keywords: italijanska književnost; Trst; Slovene literature; slovenska književnost; narodna identiteta; kulturna identiteta; karst; Kras